2020
DOI: 10.1088/1742-6596/1477/3/032012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Methods of Bird Repellent Devices in Optimizing Crop Production in Agriculture

Abstract: Rice field environments and bird attacks are the main problems for coverage and automatic pest control. Birds are one of several pests or destructive animals that can be found in rice fields. In general, farmers use traditional equipment such as plastic ropes and scarecrow to ward off these bird attacks. This research compares several methods of bird detection through camera sensors and chooses the best method in terms of accuracy, then applies it to repel birds automatically by utilizing sound frequencies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…With the idea of implementing deep learning algorithms on embedded platform, we briefly describe some of the works that utilizes deep learning on embedded platforms related to Agriculture. The use of RPi has also been demonstrated by [43] by using devices to repel birds in optimizing crop production in Agriculture. RPi and NVIDIA Jetson TX2 were used in [44] to monitor and detect Asian citrus psyllid pests in orchards using convolutional neural networks.…”
Section: Related Workmentioning
confidence: 99%
“…With the idea of implementing deep learning algorithms on embedded platform, we briefly describe some of the works that utilizes deep learning on embedded platforms related to Agriculture. The use of RPi has also been demonstrated by [43] by using devices to repel birds in optimizing crop production in Agriculture. RPi and NVIDIA Jetson TX2 were used in [44] to monitor and detect Asian citrus psyllid pests in orchards using convolutional neural networks.…”
Section: Related Workmentioning
confidence: 99%
“…The literature, by extension, includes comprehensive articles addressing both the detection and the scaring of birds [ 30 ]. One of these sources is referenced in study [ 31 ], which characterizes the prototype of a device that comprises PIR sensors as the detector to track moving birds and uses LC oscillator type colpitts with a piezo ultrasonic sensor as the repeller.…”
Section: Previous Researchmentioning
confidence: 99%
“…The comparison results found that YOLO has the highest speed performance, while mask R-CNN has the best detection ability 31 . Mask R-CNN and YOLOv3 were used to detect birds, and the results indicated mask R-CNN had superior detection capabilities to YOLOv3 32 .…”
Section: Introductionmentioning
confidence: 99%